POTENSI KAVAIN DALAM PIPER METHYSTICUM SEBAGAI TATALAKSANA PREVENTIF GENERALIZED ANXIETY DISORDER - Mahendika, Devin (Essential: Essence of Scientific Medical Journal; Vol 20 No 1 (2022): Volume 20 No. 1 (Januari - Juli 2022) Essential: Essence of Scientific Medical Journal, 2022)
Introduction: Generalized Anxiety Disorder (GAD) wa s a psychiatric disorder characterized by anxiety, motor tension , and autonomic overactivity. Piper methysticum was a plant that ha d efficacy in various therapies including GAD because of its chemical substance c avaine. C avaine wa s a biological ingredient in Piper methysticum which ha d potent anxiolytic activity. Piper methysticum extract can be used as a preventive therapy for GAD due to its anxiolytic effect on the symptoms of GAD. Discussion: Piper methysticum in its efficacy was able to potentiate GABA A R s without subtype selectivity, besides that the concentration of GABA responds to the performance of 4?2? GABA A R s significantly, so that the performance of cavaine works effectively and sensitively in the target system in addition to the 1?2?2L receptor. C avaine also showed a modest increase in GABA concentrations below EC45, but it did not affect EC50 and maximal efficacy of GABA. In addition, the chalcone synthase chain which is broken due to neurodegeneration by the RpBASi enzyme which can extend a single polypeptide chain can be repaired by c avaine. Another effect of cavaine wa s that it can modulate volt-gated calcium and sodium channels and antagonize Ca 2+ channels. Another important activity of cavaine was being able to bind to GABA receptors in the central nervous system besides functioning as an anxiolytic in the serotonergic and glutamanergic pathways. Piper methysticum in its properties is able to potentiate GABA A R s without subtype selectivity, besides that the concentration of GABA responds to the performance of 4?2? GABA A R s significantly, so that the performance of cavaine works effectively and sensitively in the target system in addition to the 1?2?2L receptor. C avaine also showed a modest increase in GABA concentrations below EC45, but it did not affect EC50 and maximal efficacy of GABA. In addition, the chalcone synthase chain which was broken due to neurodegeneration by the RpBASi enzyme which can extend a single polypeptide chain can be repaired by c avaine. Another effect of cavaine , that it was able to modulate volt-gated calcium and sodium channels and acts as an antagonist to Ca 2+ channels. Another important activity of cavaine was its ability to bind to GABA receptors in the central nervous system in addition to functioning as anxiolytics in serotonergic and glutamanergic pathways. Conclusion: The use of Piper methysticum as an effort to prevent GAD has proven to be superior because it was cheap and easy to obtain, ha d no side effects, and ha d high effectiveness in reducing GAD in accordance with its effects and clinical features. Therefore, further research on clinical trials of the use of Piper methysticum continues to be developed so that it can be implemented ethically to prevent GAD. Keywords: Piper methysticum, c avaine, GAD